Profiling of H3K4me3 and H3K27me3 and Their Roles in Gene Subfunctionalization in Allotetraploid Cotton - Zhang, Aicen; Wei, Yangyang; Shi, Yining; Deng, Xiaojuan; Gao, Jingjing; Feng, Yilong; Zheng, Dongyang; Cheng, Xuejiao; Li, Zhaoguo; Wang, Tao; Wang, Kunbo; Liu, Fang; et al. (Frontiers in Plant Science, 2021)
Cotton is an excellent model for studying crop polyploidization and domestication. Chromatin profiling helps to reveal how histone modifications are involved in controlling differential gene expression between A and D subgenomes in allotetraploid cotton. However, the detailed profiling and functional characterization of broad H3K4me3 and H3K27me3 are still understudied in cotton. In this study, we conducted H3K4me3- and H3K27me3-related ChIP-seq followed by comprehensively characterizing their roles in regulating gene transcription in cotton. We found that H3K4me3 and H3K27me3 exhibited active and repressive roles in regulating the expression of genes between A and D subgenomes, respectively. More importantly, H3K4me3 exhibited enrichment level-, position-, and distance-related impacts on expression levels of related genes. Distinct GO term enrichment occurred between A/D-specific and homeologous genes with broad H3K4me3 enrichment in promoters and gene bodies, suggesting that broad H3K4me3-marked genes might have some unique biological functions between A and D subgenome. An anticorrelation between H3K27me3 enrichment and expression levels of homeologous genes was more pronounced in the A subgenome relative to the D subgenome, reflecting distinct enrichment of H3K27me3 in homeologous genes between A and D subgenome. In addition, H3K4me3 and H3K27me3 marks can indirectly influence gene expression through regulatory networks with TF mediation. Thus, our study provides detailed insights into functions of H3K4me3 and H3K27me3 in regulating differential gene expression and subfunctionalization of homeologous genes, therefore serving as a driving force for polyploidization and domestication in cotton.